The Caring Organization: Singularity, Incompleteness and Responsibility or why 5+1 is not always 6 - Devisch, Ignaas (International Journal of Humanities and Social Science Research, 2015)
This article examines what is called the ‘caring organization’ out of the work of French philosopher Jean-Luc Nancy. Starting from two tales from Kafka and Borges, it analyzes Nancy’s concept of community and singularity and their potential relevance for the area of social sciences. Thinking an organization from the perspective of singularity means that we no longer think in terms of an unchangeable essence. Nancy’s notion of the singular goes the other way round: organizations are able to function because they differ from themselves and change all the time. An organization is but its components with their singular traits at every moment and these traits produce a singularized and thus necessarily temporary collective. As long as we start from identity as a substantial given, an unfruitful opposition is at work: the collective, the organization, is seen as the enemy of the subject and vice versa. Nancy’s notion of singularity on the contrary, does not start from an opposition of two identities but from identities differing from themselves because they are understood as singular, changing entities; their singular characteristics potentially modify the whole as such.